Are All Code-Switches Processed Alike? Examining Semantic v. Language Unexpectancy - Valdés Kroff, Jorge R.; Román, Patricia; Dussias, Paola E. (Frontiers in Psychology, 2020)
Prior studies using the event-related potential (ERP) technique show that integrating sentential code-switches in online processing lead to a broadly distributed late positivity component while processing semantically unexpected continuations instead lead to the emergence of an N400 effect. While the N400 is generally assumed to index lexico-semantic processing, the LPC has two different interpretations. One account suggests that it reflects the processing of an improbable or unexpected event while an alternative account proposes sentence-level reanalysis. To investigate the relative costs of semantic to language-based unexpectancies (i.e., code-switches), the current study tests 24 Spanish-English bilinguals in an ERP reading study. Semantically constrained Spanish frames either varied in their semantic expectancy (high vs low expectancy) and/or their language continuation (same language vs code-switch) while participants’ electrophysiological responses were recorded. The Spanish-to-English switch direction provides a more naturalistic test for integration costs to code-switching as it better approximates the code-switching practices of the target population. Analyses across three time windows show a main effect for semantic expectancy in the N400 time window and a main effect for code-switching in the LPC time window. Additional analyses based on the self-reported code-switching experience of the participants suggested an early positivity linked to less experience with code-switching. The results suggest that not all code-switches lead to similar integration costs and that prior experience with code-switching is an important additional factor that modulates online processing.